A gamificação como estratégia pedagógica: novas formas de aprender e ensinar nas aulas de educação física - Rodrigues, Amanda Marinho (2024)
In view of the technological evolution present in everyday, a great challenge arises for education professionals: to enable innovative and challenging learning situations with the use of technologies, which come closer to the reality experienced by current generations. In that regard, several methodologies present themselves as mediators of the knowledge construction process. Among these, one that has been gaining great popularity, mainly because it provides great motivation and engagement among students is the denominated gamification. Therefore, the objective of this research was to analyze the possibilities for teaching Physical Education at school, articulated with the principles of gamification, for students of 6th grade at a Full-time School in the County of Sobral, through a gamified didactic sequence, using the digital game Minecraft as proposal. The present research, regarding the source of information used, can be classified as field research; regarding the approach used, it is of qualitative nature. Furthermore, this research was guided by principles of action research. Said that, the methodological path of this research was composed of 7 (seven) steps, which are described below: 1- Bibliographic survey; 2- Contact with the management of the school where the research was carried out, in possession of a Research Authorization Term; 3- Delivery and receipt of the Free and Informed Consent Form (TCLE) and Free and Informed Consent Form (TALE) to those responsible for the research participants; 4- Preparation of the educational product (Logical organization of the didactic sequence); 5- Application of the educational product (Didactic sequence); 6- Data collection and grouping of data found and 7- Analysis of data found. An initial questionnaire and a questionnaire at the end of the practical activities were used for data collection, the field diary and to complement a smartphone to capture the best information obtained with greater fidelity and veracity of the information. In summary, the results presented showed that the games applied were well accepted by students and that we achieved to dynamize classes as a way of attracting the attention of the majority of students. It was also noted, through the evaluation carried out, that there is a need for adjustments in the game to achieve a higher average in some items in the next evaluation, since they are all important to ensure meaningful and motivating learning for students, as well as expanding the possibilities of reflections and actions for students. We understand that the methodologies applied to gamification are not capable of solving current teaching problems, but incorporated into a set of procedures, they are situated as a motivational and enriching factor for pedagogical work, bringing the school and the teacher closer to the student's daily life, through an efficient and dynamic dialogue, since technologies require new thoughts and attitudes.